STRATEGI PENANGANAN PERILAKU MENYIMPANG PESERTA DIDIK MELALUI GURU SEBAGAI ROLE MODEL - Endang Setyowati; Dwi Ulfa Nurdahlia (IKIP Budi Utomo Malang, 2018)
Deviant behavior is defined as behavior, actions, or someone in response to the environment contrary to the norms and laws that exist in society. Amid public life still occasionally encountered measures are not in accordance with the rules (norms) in effect on the community, for example a students cheat on quizzes, lying, stealing, and disturbing other students. Spot, the role of teachers is necessary and can be done through education and will appear, when the teacher managed to create a positive character on learners, for example learners will be an honest individual (not cheating on replay, lying, stealing) and disturbing other students. Therefore, teachers become good role models, pay attention to several criteria such as: having a good personality, including how to speak, how to relate with learners, behavior, etchics are high, kind, friendly, trustworthy, resolute, sincerity in teaching, course of action that leads to a positive attitude and so on.